Development of a method and equipment for measuring the neutron flux from a research reactor - Shinbulatov, S.K.; Saduyev, N.O.; Kalikulov, O.A.; Sedov, A.N.; Oskomov, V.V.; Mukhamejanov, E.S.; Baktoraz, A.E.; Yerezhep, N.O.; Utey, Sh.B.; Shaimerdenov, A.A.; Aitkulov, M.T.; Myktybekov, D.E.; et al. (Recent Contributions to Physics, 2023)
In this paper, a new method for measuring the neutron flux using proportional counters SNM-18 filled with 3Ne is studied. When developing equipment for automated measurement of the neutron flux of the research reactor VVR-K, the determining optimization criteria are power consumption, weight and dimensions. For this purpose, devices were used for automated measurement of the equivalent of soil moisture and the equivalent of snow water by the neutron component of cosmic rays. A number of experimental studies have been carried out to determine the optimal levels of supply voltages, the design of the device for operation at the VVR-K reactor has been changed. The main elements of the neutron detector design are a block of a hydrogen-containing moderator; a tube of a proportional thermal neutron counter; an amplifier and a microcontroller for analyzing the signal from the detector; a high-voltage power supply and a transmitter. Special software has also been developed for simultaneous control of detectors. Test measurements of the neutron flux were performed at the research reactor plant VVR-K INP using a Pu-Be neutron source, with an intensity of 1.8 *106 n/s. To reduce the neutron intensity for the safety of personnel and to reduce the load on the detector, the neutron source was placed inside a boron polyethylene collimator. Key words: neutron flux, reactor, proportional counter SNM-18.